Perspectives on Kashmir - Yusuf, K. F. (Islamabad, Pakistan : Pakistan Forum, 1994)
Collection of articles and speeches delivered at a seminar on various aspects of Kashmir dispute.
Keywords: Jammu and Kashmir (India) -- Politics and government